Asupan Gizi, Usia Kehamilan dan Usia Anak Terkecil Sebagai Prediktor Pertumbuhan Janin di Kota Pangkalpinang - Erfila Erfila; Rostika Flora; Rico Januar Sitorus (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aimed to confirm various predictors that affect fetal growth in pregnant women in Pangkalpinang City, Bangka Belitung Islands. This observational analytic study with a cross-sectional design was conducted in December 2022. The subjects of the study were 121 pregnant women who were selected using the simple random sampling technique. The data in this study consisted of the size of the abdominal circumference as an indicator of fetal growth and is the dependent variable. Indicators of energy intake, protein, fat, carbohydrate, Fe, Ca, Vitamin C, the difference in weight, height, MUAC, Hb levels, blood pressure, the youngest child, age of pregnant women, and husband were determined as independent variables. A backward regression model with the IBM SPSS Statistics version 25 program defined risk factors as predictors. The results showed that energy and carbohydrate intake, gestational age, and the youngest child were responsive predictors of fetal growth in Pangkalpinang City with the regression model ?=-2,338+0,003X_1-0,025X_4+0,841X_16+0,210X_17. This research recommends that policymakers consider improving the socioeconomic conditions of families, especially mothers' education, family income, and social affiliation.